9a(ab+3)(3ab-2)=

Simple and best practice solution for 9a(ab+3)(3ab-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9a(ab+3)(3ab-2)= equation:


Simplifying
9a(ab + 3)(3ab + -2) = 0

Reorder the terms:
9a(3 + ab)(3ab + -2) = 0

Reorder the terms:
9a(3 + ab)(-2 + 3ab) = 0

Multiply (3 + ab) * (-2 + 3ab)
9a(3(-2 + 3ab) + ab(-2 + 3ab)) = 0
9a((-2 * 3 + 3ab * 3) + ab(-2 + 3ab)) = 0
9a((-6 + 9ab) + ab(-2 + 3ab)) = 0
9a(-6 + 9ab + (-2 * ab + 3ab * ab)) = 0
9a(-6 + 9ab + (-2ab + 3a2b2)) = 0

Combine like terms: 9ab + -2ab = 7ab
9a(-6 + 7ab + 3a2b2) = 0
(-6 * 9a + 7ab * 9a + 3a2b2 * 9a) = 0
(-54a + 63a2b + 27a3b2) = 0

Solving
-54a + 63a2b + 27a3b2 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '9a'.
9a(-6 + 7ab + 3a2b2) = 0

Factor a trinomial.
9a((-3 + -1ab)(2 + -3ab)) = 0

Ignore the factor 9.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(-3 + -1ab)' equal to zero and attempt to solve: Simplifying -3 + -1ab = 0 Solving -3 + -1ab = 0 Move all terms containing a to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1ab = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1ab = 0 + 3 -1ab = 0 + 3 Combine like terms: 0 + 3 = 3 -1ab = 3 Divide each side by '-1b'. a = -3b-1 Simplifying a = -3b-1

Subproblem 3

Set the factor '(2 + -3ab)' equal to zero and attempt to solve: Simplifying 2 + -3ab = 0 Solving 2 + -3ab = 0 Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3ab = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3ab = 0 + -2 -3ab = 0 + -2 Combine like terms: 0 + -2 = -2 -3ab = -2 Divide each side by '-3b'. a = 0.6666666667b-1 Simplifying a = 0.6666666667b-1

Solution

a = {0, -3b-1, 0.6666666667b-1}

See similar equations:

| x^(3/4)-x^(1/4) | | 3y-3+y=22+2y-3y | | 2(3x+4)-5=6x+3 | | 7-7q=-15+-15q | | 2=3u+8 | | -30x+-60+9=30 | | .25x+.1x+.05x=14 | | 64-12*2-6/3=x | | y-7=-2(x-2) | | 8.7n+4.5-3.2n=37.5 | | X-3.5=2.25 | | 5(-6d+12)= | | -35+4x=-2x+31 | | Y+6=3(x-2) | | 8.7n+4.5-3.2n=375 | | 3y+7=x-13 | | P=$1440/4 | | 3(2y+1)-5(12y-7)+(6y-1)=37 | | P=$1440/5 | | 13.2=t4.4 | | -4r-9=-14-3r | | x+4+3x=31 | | -2x-17=13-4x | | 4s^2=-36 | | -2Xx=5 | | 12-9x+45=-1+x | | R+25=9 | | 3x+1+4x=7x-3 | | 5d=9/10 | | 6x-17=13-4x | | 27.50x+23.25x=17 | | -9b=153 |

Equations solver categories